Accelerated learning versus early promotion of the child in preschool education: impact on comprehensive development - Vergara Ortiz, Maiduth; Soto Cortés, Elizabeth (Revista UNIMAR, 2023)
The objective of this research article is to compare the foundations provided by accelerated learning, with the integral development pursued by the Colombian educational system. For this, a field investigation based on the mixed method was carried out. As data collection instruments, a semi-structured interview was applied to ten teachers from private educational institutions in the tourist and cultural district of Riohacha, and an observation guide with a Likert scale, for children who were subject to the early promotion. The results show that some of them present a cognitive development in line with the grade they are in; however, they manifest deficiencies in social integration with the group, which could be affecting their emotional development.